Large Orbital Pediatric Intraosseous Hemangioma - Colin Bacorn; Lily Koo Lin (Case Reports in Ophthalmological Medicine)
A five-year-old male presenting with progressive right facial swelling underwent multiple biopsies before being diagnosed with a polyostotic frontal-zygomatic primary intraosseous hemangioma. Intraosseous hemangiomas are rare, more frequently afflict adult females, and very rarely involve the orbit. Our case with bony destruction and surrounding soft tissue mass measured 5.3 cm in a child mimicked a more ominous malignancy. This case is unique with its rapid progression and largest reported size, leading to additional challenges such as difficulty in achieving an adequate tissue sample and in the surgical management with respect to significant blood loss in a small child.